Concerning one method of final grade giving to undergraduate students - Dadyan E. G. (Interactive science, 2016)
this paper proposes methods to increase the objectivity of assessment of graduation examination and the graduation qualifying work of bachelor, realized by using a special information system developed by author as an application of the system “1C: Enterprise”.
Keywords: motivation; методика оценки Госэкзамена; методика расчета набранных баллов; мотивация работы студента; методика оценки выпускной квалификационной работы; method of calculation of scores; student work; assessment methodology of the qualification work; state exam assessment method